Effect of Stirring Rate and Freezing Time on the Percentage of Recovery of Residual Oil from Palm Oil Mill Effluent via a Stirred Freeze Crystallizer - Mohamed Anuar, M.A. (Institute of Physics Publishing, 2020)
In palm oil industries, treating palm oil mill effluent (POME) is still problematic due to both technologies sustainability and management will. In conjunction with the POME problem, increasing the oil extraction rate (OER) is also the most crucial task for these palm oil production community. The most promising method to address these two challenges is by direct recovering of lost oil in the POME. Among the popular separation processes for recovery of residual oil from POME are by using evaporation, adsorption and reverse osmosis as process media generated a good amount of percentage recovery of residual oil from the effluent. However, these methods require high amount of energy and the process itself are complex where it can affect the quality of the residual oil. The goal of this project is to extract and recover the residual oil in POME using an advanced approach called progressive freezing, in order to meet the standard quality discharged of effluent and improve oil extraction rate (OER). In this research, a cylindrical stirred freeze crystallizer was designed and fabricated, where the crystallizer was immersed in a refrigerated water bath for cooling purpose. The effect of stirring rate and freezing time on the percentage of recovery of residual oil was investigated. It was found that higher stirring rate resulted in a lower percentage oil recovery, which translated into low efficiency. On the other hand, higher percentage of oil recovery was monitored as the freezing time is prolong from 20 to 60 minutes. The highest percentage oil recovery of 76.5 was obtained at coolant temperature of 2Â°C, freezing time of 40 minutes and the stirring rate of 150rpm. Â© 2020 IOP Publishing Ltd.